2018
DOI: 10.4103/1673-5374.230271
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap: axonal fusion drives rapid functional recovery of the nervous system

Abstract: Injuries to the central or peripheral nervous system frequently cause long-term disabilities because damaged neurons are unable to efficiently self-repair. This inherent deficiency necessitates the need for new treatment options aimed at restoring lost function to patients. Compared to humans, a number of species possess far greater regenerative capabilities, and can therefore provide important insights into how our own nervous systems can be repaired. In particular, several invertebrate species have been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Cell repair elicited by PM insults also employs exofacial PS. Exposure of PS on injured axons initiates axonal fusion, a highly efficient mechanism of nervous system repair (reviewed, ( 152 , 153 )). This finding is especially interesting because this fusion process involves the C. elegans fusogen EFF-1, and to the best of our knowledge, this is the only indication in the literature suggesting that fusions mediated by “Fusion Family” (FF) proteins (including C. elegans EFF-1 and AFF-1 and gamete-expressed HAP2) may, as all other fusion processes discussed above, depend on PS exposure.…”
Section: Phosphatidylserine Signaling As a Uniquely Conserved Signalimentioning
confidence: 99%
“…Cell repair elicited by PM insults also employs exofacial PS. Exposure of PS on injured axons initiates axonal fusion, a highly efficient mechanism of nervous system repair (reviewed, ( 152 , 153 )). This finding is especially interesting because this fusion process involves the C. elegans fusogen EFF-1, and to the best of our knowledge, this is the only indication in the literature suggesting that fusions mediated by “Fusion Family” (FF) proteins (including C. elegans EFF-1 and AFF-1 and gamete-expressed HAP2) may, as all other fusion processes discussed above, depend on PS exposure.…”
Section: Phosphatidylserine Signaling As a Uniquely Conserved Signalimentioning
confidence: 99%
“…Peripheral nerve regeneration is a complex process involving restoring the interrupted neuronal connectivity and resulting in functional recovery 34 . Treatments for nerve transection injury have addressed a variety of scientific disciplines, including reconstructive microsurgery, transplantation, biomaterial science, physical therapy, and genetic pharmacotherapy 35 - 37 . Previous studies have demonstrated that hypoxic stress may induce the expression of multiple genes and affect functional recovery of axon regeneration through HIF pathway 11 , 13 , 14 , 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In certain invertebrate species, WD does not occur for weeks to months after an axon is severed. The regenerating axons frequently make contact with intact distal segment axons and auto-fuse, which restores axon continuity between proximal and distal segments and enables recovery of nerve function within days [ 4 - 6 ]. Auto-fusion occurs with high specificity, as existing evidence suggests that regenerating axons can recognize and fuse with their original distal ends.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, invertebrates such as C elegans do not have injury-induced immune responses that are present in mammals [ 6 ]. Overall, the immune response to PNI in mammals is conducive to successful nerve regeneration [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation